Chlorpyrifos degradation under the influence of climate factors and fertilizer regimes in a tropical vertisol. (22nd March 2020) - Kollah, Bharati; Ahirwar, Usha; Singh, Neera; Dubey, Garima; Patra, Ashok; Mohanty, Santosh Ranjan
Abstract: Biodegradation of chlorpyrifos under the influence of fertilizer application and climate factors such as elevated CO2, temperature and moisture was studied. Soybean was grown in control, inorganic, organic and integrated (both inorganic and organic) fertilized fields. Rhizospheric soils collected during the vegetative growth phase were amended with chlorpyrifos (10 μg/g soil) and incubated under different climate factors. The climate factors were CO2 concentration (400, 800 ppm), temperature (25, 45°C) and moisture-holding capacity (60, 100%). Chlorpyrifos degradation rate varied from 0.28 to 0.65 μg/g soil/d. The abundance of 16S rRNA gene copies of eubacteria varied from 13 × 10 6 to 7 × 10 5 /g soil. Actinomycetes-specific 16S rRNA gene copies were in the range of 62.5 × 10 5 to 18.5 × 10 3 /g soil. Microbial abundance was high in organic amended soil and low in control soil irrespective of climate factors. Elevated CO2 and high temperature inhibited ( P < 0.05) chlorpyrifos degradation rate and the abundance of 16S rRNA genes of eubacteria and actinomycetes. Chlorpyrifos degradation followed as: organic > integrated > inorganic > control. The degradation rate was positively correlated ( P < 0.01) with the soil organic C, available N, water-stable aggregates and mean weight diameter of the soil aggregates of soil. Principal component analysis denoted temperature and fertilizer as the major components of variation. The study highlights that elevated CO2 and temperature affect chlorpyrifos biodegradation; however, the effect can be alleviated by the amendment of organic fertilizer.